Media Across the African Diaspora : content, audiences, and global influence - Banjo, Omotayo O. (New York : Routledge, 2019)
This volume gathers scholarship from varying disciplinary perspectives to explore media owned or created by members of the African diaspora, examine its relationship with diasporic audiences, and consider its impact on mainstream culture in general. Contributors highlight creations and contributions of people of the African diaspora, the interconnections of Black American and African-centered media, and the experiences of audiences and users across the African diaspora, positioning members of the Black and African Diaspora as subjects of their own narratives, active participants and creators. In so doing, this volume addresses issues of identity, culture, audiences, and global influence
Part I. Contributions to mainstream media culture -- Part II. Owning images and narratives -- Part III. Bridges across the African diaspora -- Part IV. Digital diaspora
Includes bibliographical references and index.
Keywords: African American mass media; African Americans in mass media; Black mass media; Black people in mass media; Ethnic mass media -- United States